Reboot : a blueprint for happy, human business in the digital age - Stockwood, Jason, ....- (London : Virgin Books, 2018)
The tech revolution will hit us all soon. How can any organisation survive and thrive? Headlines predict that whole industries will be decimated by Artificial Intelligence and automation. Some bosses and bankers are rubbing their hands at the prospect of cost savings and staff cuts. But there is another way. New technology can also empower teams, fuel creativity and make people happier. At Simply Business, twice voted the UK's best company to work for, big data and automated systems are being harnessed to generate positive growth, with all staff moving to a four-day week on the same pay. In this bold blueprint, CEO Jason Stockwood – named by the Sunday Times as the UK's best leader – shows how any organisation can think freshly and benefit from technology by putting its people first.
Keywords: Business management; Digitalisering